Understanding AI-Driven Threat Detection and Response Systems: A Technical Deep Dive - Deepak Gandham, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of artificial intelligence-driven threat detection and response systems in modern cybersecurity environments. The article examines the evolution of security infrastructure through the integration of advanced machine learning algorithms and automated response mechanisms. The article investigates the effectiveness of multi-tiered machine learning architectures in threat detection, behavioral analysis frameworks for user and device monitoring, and automated response capabilities. The article demonstrates significant improvements in detection accuracy, response times, and false positive reduction through AI optimization. The article indicates that the integration of quantum computing and advanced AI capabilities presents promising developments for future security systems, while maintaining operational efficiency and scalability across enterprise deployments.
Keywords: Artificial Intelligence Security; Behavioral Analytics; Automated Threat Response; Machine Learning Detection; Quantum Cybersecurity